Análisis jurídico de los principios de igualdad, progresividad y no regresividad en el acceso al cambio de régimen semiabierto en el COIP - Armijos Coronel, Luz Marylin (2023)
The present Degree Work denominated: “Legal analysis of the principles of quality, progressivity and non-regressivity in the acess to the change of semi-open regime in the COIP”, whose study arises investigate due to the fact that under the Organic Reformatory Law to the Comprehensive Organic Penal Code in a specific way in articles 113 and 114 of this Law, articles 698 and 699 of the Organic Integral Penal Code are modified, referring to the access to the progressive regimes of social rehabilitation for certain crimes that have been restricted to access this penitentiary benefit, where the principle of equality and non- discrimination is violated for those deprived of liberty that despite being in the same situation and belonging to a group of priority attention are not guaranteed access to change of semi- open and open regimes; the principle of progressiveness is undermined, since the new amended law suppresses and eliminates these benefits that were previously granted to everyone without any limit as part of social rehabilitation and compliance with the penitentiary treatment axes. The Penitentiary System in Ecuador is going through a crisis due to the increase of criminality and the high rates of overcrowding in prisons, which in most cases is due to the delay in the processing of the semi-open and open regimes, even more so now because prisoners will not be able to access these benefits due to the reform made to the Organic Integral Penal Code, which has not considered that the execution of sentences will be governed by the penitentiary regimes necessary for the rehabilitation and subsequent reintegration of the convicted person. In addition, it is necessary to indicate that since treatment is a voluntary modality, the prisoners who are prohibited from accessing prison benefits will not take part in all the activities involved and, therefore, it would be useless to keep them in a closed regime if they will undoubtedly not comply with the rehabilitative axis or with the purposes of the sentence, among the main one, the non-commission of subsequent crimes. In the present Degree Project, both materials and methods that allowed the development of the research were applied, in the same way field techniques such as surveys and interviews directed to professionals of Law and Clinical Psychology were used, the results obtained were useful to be able to raise the legal proposal that tends to guarantee the access of all those deprived of liberty to the progressive regimes of social rehabilitation regardless of the criminal offense committed.